The CLARIS LPB database: constructing a long-term daily hydro-meteorological dataset for La Plata Basin, Southern South America - Penalba, Olga Clorinda (2014)
CLARIS LPB database was built within the framework of the CLARIS LPB project “A Europe-South America Network for climate Change Assessment and Impact Studies in La Plata Basin” of the European Community's Seventh Framework Programme (FP7). The main variables available in the database are rainfall, temperature, radiation, heliophany and streamflow, constituting a high-quality daily hydro-meteorological dataset for scientific purpose available at http://wp32.at.fcen.uba.ar/. The objective of this article is to describe CLARIS LPB database construction, quality control and spatial and temporal characteristics. Due to the interactions with more than 60 institutions, the network of stations expanded from 107 stations in the FP6 CLARIS to more than 9000 stations in the FP7 CLARIS LPB. More than 800 maximum and minimum temperatures series, more than 8000 rainfall series, 68 radiation series, 29 heliophany series, and 58 streamflow series are available in the database webpage. The number of stations also varied greatly as a function of time, and decadal variations were evident in both rainfall and temperature stations with at least 20% of data missing. According to the characteristics analysed, this dataset provides spatially consistent climatic time series which enable a variety of empirical climate studies. It was already used as input for hydrological models, for the validation and analysis of present-day regional and global climate model outputs, for improvement in the analysis of recent past climate variability in La Plata Basin, for analysing palaeohydrological reconstructions of the past climate variability, among others. Finally, the spatially highly dense daily database of rainfall and maximum and minimum temperatures allowed the generation of gridded products.